Compatibility of the Presence of the State Policies with the Presidential Government System in Indonesia - Ansori, Lutfil (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2023)
The presence of state policies amidst the presidential system has sparked controversies and raised glitches in state administration because these policies and the practice of parliamentarism intersect. On the other hand, fundamental issues arise from the national development planning system, calling for systemic maintenance to reinforce the direction and certainty of development in Indonesia. This article seeks to explore the compatibility of the state policies with the presidential system in Indonesia, mainly focusing on the urgency of the state policies and the form of the policies compatible with the presidential system in Indonesia. This research employed a normative method supported by statutory, historical, and conceptual approaches. To examine the urgency and the compatibility of the policies to the constitutional system in Indonesia, the policies need to be further investigated. The research results show that the urgency of the state policies can be viewed from the need to lead the directions, and policies, and set the certainty of the state development. The presence of these policies is expected to improve the shortcomings of the national development planning system, encompassing improvement of the political aspect of the development plan, constitutional design aspect, and ideological aspect. The compatibility of these policies with the presidential system represents the policies that leave no harm to the standard of the presidential system unless they (i) weaken the position of the president in connection with the parliament, and (ii) require the president to be responsible under the MPR (People’s Consultative Assembly). The compatibility of these policies can be formulated in three models: (i) the DPSP model; (ii) the parent law model as the state policies; and (iii) setting the policies by the MPR by adjusting to the principles of presidentialism.